Preventing Ischemic-Reperfusion Injury after Tourniquet Application in Fracture using Aloe vera Ethanolic Extract - Huwae, Thomas Erwin Christian Junus (Open Access Macedonian Journal of Medical Sciences, 2022)
Introduction: A tourniquet is a typical equipment used in the orthopedics surgery to decrease blood loss and create a better operating environment. Ischemic-reperfusion damage, which happens when the tourniquet is deflated, is one of the tourniquet's negative effects. Antioxidants can be used to minimize oxidative stress, which is one strategy to mitigate ischemic-reperfusion injury. Aloe vera, for example, is widely known for its antioxidant and anti-inflammatory properties. Method: The tibias of male Wistar strain rats (Rattus norvegicus) were fractured in this experiment, and Aloe vera gel was given orally as an antioxidant. A total of 18 rats were utilized in this research, which were separated into 6 groups. Varying amounts of Aloe vera extract were given to the treatment groups: 40 mg/kgBW, 60 mg/kgBW, and 80 mg/kgBW. The tourniquet would be inflated for two hours then deflated after application of the Aloe vera extract. Superoxide dismutase (SOD) and malondialdehyde levels were measured in the tibia (MDA). Result: Application of tourniquet increased oxidative stress marker in fracture state, marked by reduction of SOD and increase of MDA. After administration of Aloe vera extract, the oxidative stress parameters (SOD and MDA) were reduced significantly. Conclusion: The result of this study suggests that tourniquet increased oxidative stress marker in fracture state and Aloe vera extract could be used to ameliorate this ischemic-reperfusion injury.